The innovation of rehal NEO visual disabled-friendly - Sabaruddin, Siti Nor Azimah; Mohd Hashim, uhammad Haneef Taqiyuddin; Aziz, Nur Anis Huda; Arupudin, Ain Nurfatehah; Kamaruzaman, Nurul Athirah (Pusat Asasi, UiTM Cawangan Dengkil, 2020)
Rehal Neo is one of the innovations inspired by the original rehal available in the market. It is created for everyone especially for the disabled including the blinds to give convenience for them to read al-Quran. In the Quran in Surah Al-Qamar, stated that the Quran is a reminder for all mankind. With the creation of Rehal Neo, it will be easier for the visually disabled groups to place their al-Quran while reading it. This is because the Braille al-Quran is physically heavy, thick and big compared to the normal cited al-Quran. The design of Rehal Neo which is flexible, made with lightweight materials, is portable for the OKU groups to handle and carry around since the design is made similar to a briefcase. Moreover, Rehal Neo has the added values which the making of Rehal Neo uses the electronic component combined with a hinge that will simplify the uses of the rehal by only pushing the button to automatically open the briefcase into rehal shape and push the button once again to keep it back close as a briefcase when the are not in-used. This is contrary to the original available rehal in the market since the original one is usually heavy, making it hard for the OKU groups to carry them around everywhere. The results of this innovation are giving a big advantage to all types of groups, not only for the normal people but also for the OKU groups including those who are visually disabled.